Silent Ozu three crime dramas = Hijôsen no onna - Ozu, Yasujirō 1903-1963; Brand, Neil 1958- (<<The>> Criterion Collection, 2015)
"This formally accomplished and psychologically complex gangster tale pivots on the growing attraction between Joji, a hardened career criminal, and Kazuko, the sweet-natured older sister of a newly initiated young hoodlum-a relationship that provokes the jealousy of Joji's otherwise patient moll, Tokiko. With effortlessly cool performances and visual inventiveness, "Dragnet Girl" is a bravura work from Yasujiro Ozu." [criterion.de]
Original: Japan 1933
Bildformat 1.33:1
Keywords: Film; DVD-Video